Long-Term Use of The Ketogenic Diet - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2006)
A retrospective chart review of 28 children (15 males, 14 females) treated with the ketogenic diet for epilepsy for more than 6 years was conducted at Johns Hospital Hospital.